Queer theory, gender theory an instant primer - Wilchins, Riki Anne (Alyson Books, 2004)
Queer Theory, Gender Theory: An Instant Primer is a classic of LGBTQ+ literature and is taught in most gender studies programs throughout the United States. It was the first book to offer a one-stop, no-nonsense introduction to the core of postmodern theory, particularly its impact on queer and gender studies and is still powerfully relevant today. Nationally-known gender activist Riki Wilchins combines straightforward prose with concrete examples from LGBTQ+ and feminist politics, as well as her own life, to guide the reader through the foundational ideas of Derrida, Foucault, and Judith Butler that have forever altered our understanding of bodies, sex and desire. This is that rare postmodern theory book that combines accessibility, passion, personal experience and applied politics, noting at every turn why these ideas matter and how they can affect your daily life.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; fem1000; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; thématiques; théories féministes; états-unis